2023
DOI: 10.1038/s41597-023-01948-z
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional chromatin architecture datasets for aging and Alzheimer’s disease

Abstract: Recently, increasing studies are indicating a close association between dysregulated enhancers and neurodegenerative diseases, such as Alzheimer’s disease (AD). However, their contributions were poorly defined for lacking direct links to disease genes. To bridge this gap, we presented the Hi-C datasets of 4 AD patients, 4 dementia-free aged and 3 young subjects, including 30 billion reads. As applications, we utilized them to link the AD risk SNPs and dysregulated epigenetic marks to the target genes. Combinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…S4). Additionally, several independent studies have also demonstrated chromosomal interactions within this APOE locus [43,44]. Our findings suggest that these four APOE locus genes are located within a single TAD, creating a 3D genomic environment that facilitates their coregulation.…”
Section: D Genome Structure Of the Apoe Locussupporting
confidence: 60%
See 1 more Smart Citation
“…S4). Additionally, several independent studies have also demonstrated chromosomal interactions within this APOE locus [43,44]. Our findings suggest that these four APOE locus genes are located within a single TAD, creating a 3D genomic environment that facilitates their coregulation.…”
Section: D Genome Structure Of the Apoe Locussupporting
confidence: 60%
“…Recently, research in AD has applied this concept [75,76]. Based on evidence from chromosome conformation capture [42][43][44], it is likely that multiple genes within the APOE locus are coregulated within the same TAD. Therefore, TADs are well-suited to study the mechanisms of of multiple genes within APOE locus.…”
Section: Discussionmentioning
confidence: 99%
“…By deleting a microglia‐specific enhancer 30 kb upstream of BIN1 promoter, they observed a reduced BIN1 expression in microglia, but not in neurons or astrocytes. In another study, Hi‐C was performed on AD brain samples and a notable enrichment of chromatin loops upstream of the BIN1 promoter overlapping AD risk variants was reported, lending further support to the existence of long‐range regulatory mechanisms related to BIN1 106 . In a very recent study, analysis of snRNA‐seq and Hi‐C from AD brain samples revealed increased somatic mosaic gene fusion events due to DNA double stranded breaks (DSBs) in excitatory neurons.…”
Section: Single‐nucleus Transcriptomics Elucidates Cell Type–specific...mentioning
confidence: 84%
“…The maturation of chromatin conformation capture technology such as HiC has enabled the association of genomically distal CREs to genes through their spatial proximity in nuclei to target-gene promoters (Rao et al 2014; Javierre et al 2016; Kloetgen et al 2020; Xu et al 2022; Meng et al 2023). The high resource usage is one of the key limitations of these approaches.…”
Section: Introductionmentioning
confidence: 99%